The rediscovery of synchronous reluctance and ferrite permanent magnet motors : tutorial course notes /: tutorial course notes. ([2016]) - Pellegrino, Gianmario; Jahns, Thomas M; Bianchi, Nicola, 1967-; Soong, Wen L; Cupertino, Francesco
No abstract available